394 Nutritional Regulation of LH Secretion in Gilts: Hypothalamic Expression of Kisspeptin and Neurokinin B. (10th April 2018) - Lents, C A; Thorson, J F; Adams, H; Petersen, S L; Prezotto, L; Berry, E D; Nonneman, D J
Abstract: Puberty, brought about by changes in LH pulse frequency and amplitude, is metabolically gated in the pig. How nutrition regulates LH secretion to initiate puberty in gilts is largely unknown. Kisspeptin (Kiss1) and neurokinin B (NKB) are neuropeptides that have been implicated in regulating LH pulsatility. The objective was to determine if changes in pulsatility of LH in gilts caused by alterations in energy balance are associated with differences in expression of Kiss1 or NKB in the medial arcuate nucleus (mARC) of the hypothalamus. Prepubertal gilts were ovariectomized and at 150 d of age fed to either gain (full-fed; n = 6) or lose (restricted; n = 6) BW for 11 d. On day 10, serial blood samples were collected every 12 min for 6 h to quantify LH pulses. On day 11, hypothalami were collected to quantify gene expression using isotopic in situ hybridization. Differences ( P < 0.0001) in BW were achieved by day 5 and maintained for the remainder of the study. Mean concentrations ( P < 0.01) of LH were greater in restricted gilts than in full-fed gilts (1.76 ± 0.09 ng/mL vs 1.41 ± 0.08 ng/mL, respectively), but basal concentrations of LH were not different ( P = 0.59). Number of LH pulses (6.5 ± 0.5) were not different ( P = 0.12), but LH pulse amplitude was greater ( P < 0.001) in restricted gilts than full-fed gilts (2.32 ± 0.15 ng/mL vs 1.02 ± 0.14 ng/mL, respectively). Expression of Kiss1 mRNA was greater ( P < 0.02) in the more caudal sections of the mARC, but treatment did not affect expression of Kiss1. Expression of NKB mRNA was greater ( P < 0.0001) in the more caudal sections of the mARC, and expression of NKB was greater ( P < 0.05) in restricted gilts when compared with full-fed gilts. The lack of treatment effect on expression of Kiss1 in the mARC or LH pulse frequency is consistent with the idea that hypothalamic expression of Kiss1 is correlated with the number of LH pulse. Although NKB is thought to be associated with LH pulse frequency, these data indicate that amplitude of LH pulses may be regulated by NKB in the gilt. AFRI (2001-67015; CAL). USDA is an equal opportunity provider and employer.